Synthesis of para-Quinone Methides via Oxidative Ring-Opening of Spiro-cyclopropanyl-cyclohexadienones - Cui, Chaoxing; Wu, Jianli; Song, Xixi; Li, Miaomiao (Synthesis, 2022)
An efficient and simple IBX-promoted oxidative ring-opening of spiro-cyclopropanyl-cyclohexadienones was developed. Disubstituted para-quinone methides were obtained with good to excellent yields and high regioselectivity (33 examples, 45–90% yields). This convenient transformation provides a new method to construct significant para-quinone methides and features high efficiency, broad substrate scope, and good functional group compatibility
Keywords: spiro-cyclopropanyl-cyclohexadienones; para-quinone methides; IBX; oxidation; ring opening